Negligência familiar contra crianças e adolescentes – perspectivas dos/as autores/as da violência - Sabino, Fabiano Henrique Oliveira (Universidade Federal de São Carlos, 2022)
Introduction: Violence against children and adolescents involves a complexity of factors. Family negligence is included in the violation of rights and is found in an associated way, but it is often disregarded for not having physical consequences and for conceptual inconsistency. Objectives: to understand the meanings attributed to negligence against children from the perspective of families involved in this phenomenon accompanied by a Guardianship Council. Methodology: Qualitative study anchored in the Complex Paradigm, carried out with 20 authors of family neglect, referenced by the Guardianship Council. The research was carried out through a semi-structured interview and a field diary in the period of January 2021. Data analysis took place through the classification and organization of data in reference frames and establishment of relationships between the data. Results and Discussion: Two thematic categories entitled “Care and Negligence” and “Historicality and Negligence” were listed. The first showed that there are elements that understand negligence in a simplifying and normative logic, pointing out the woman as guilty of the practices of violence. This is placed as a process, needing to be seen in a multidimensional aspect. The second revealed the historical and learned character of not caring, denoting the absence of public policies to protect children and adolescents from perpetrators of neglect. There are elements that demonstrate a search for overcoming the path lived, still without interprofessional and intersectoral support. Conclusion: The multidimensionality of family neglect requires effective actions from the protection network; as long as there are insufficient and lame public policies, labeling those responsible as solely guilty of a violation of rights is irresponsible and inconsequential. The importance of seeking to make public policies and interprofessional actions effective in the context of coping, mapping and preventing violence in intrafamily relationships is reiterated, especially by Primary Health Care teams.
Family neglect against children and adolescents - perspectives of perpetrators of violence
Keywords: Criança; Adolescentes; Violência; Enfermagem; Pesquisa qualitativa; Child; Adolescent; Violence; Nursing; Qualitative research; CIENCIAS DA SAUDE::ENFERMAGEM